2022
DOI: 10.1111/1462-2920.15943
|View full text |Cite
|
Sign up to set email alerts
|

The pH signalling transcription factor PacC modulate growth, development, stress response and pathogenicity of Trichothecium roseum

Abstract: pH is one of the important environmental factors that affect the growth, development and pathogenicity of postharvest pathogen. The transcription factor PacC dominates the pH signal pathway. PacC in Trichothecium roseum showed three typical conserved zinc finger domains and closest homology to Fusarium graminearum. T. roseum increased the environmental pH both in vitro and in vivo. Expression patterns of TrpacC under different pH showed that at increasing pH from 3 to 5, the wild-type (WT) strain induced the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Under such acid environment, polygalacturonase secretion was enhanced and pectin in fruits was actively hydrolyzed and fruit decay occurred. Wang et al [13] also reported that at acidic environment (pH 4.0), expression the TrPacC gene encoding the same pH signaling transcriptional activator PacC in Trichothecium roseum was promoted. The tissue acidification is a significant factor in determining virulence of P. expansum.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Under such acid environment, polygalacturonase secretion was enhanced and pectin in fruits was actively hydrolyzed and fruit decay occurred. Wang et al [13] also reported that at acidic environment (pH 4.0), expression the TrPacC gene encoding the same pH signaling transcriptional activator PacC in Trichothecium roseum was promoted. The tissue acidification is a significant factor in determining virulence of P. expansum.…”
Section: Discussionmentioning
confidence: 96%
“…The results were constant with those reported by Saur et al [6] and Wang et al [7] However, it has been reported that the acidic environment (pH 3.0) inhibits the growth of Trichothecium roseum. [13] Barad et al [35] also reported that the GOX2 gene responsible for glucose oxidase was highly expressed under alkaline conditions, leading to secretion of high level of gluconic acid and drop in pH in the medium. Under such acid environment, polygalacturonase secretion was enhanced and pectin in fruits was actively hydrolyzed and fruit decay occurred.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, the transformation of T. roseum with fluorescent proteins was based on the PEG-mediated protoplast transformation method (Dai et al, 2019(Dai et al, , 2020Wang et al, 2022). Agrobacterium tumefaciens-mediated transformation (ATMT) methods were repeatedly utilized for transfer GFP into biocontrol agents to reveal the interactions between parasites and powdery mildews (Németh et al, 2019).…”
Section: Green Fluorescent Protein Transformation Of T Roseum By the ...mentioning
confidence: 99%